Safety and immunogenicity of a trivalent virus-like particle vaccine against western, eastern, and Venezuelan equine encephalitis viruses: a phase 1, open-label, dose-escalation, randomised clinical trial. Issue 8 (August 2022) - Coates, Emily E; Edupuganti, Srilatha; Chen, Grace L; Happe, Myra; Strom, Larisa; Widge, Alicia; Florez, Maria Burgos; Cox, Josephine H; Gordon, Ingelise; Plummer, Sarah; Ola, Abidemi; Yamshchikov, Galina; et al.
Summary: Background: Western (WEEV), eastern (EEEV), and Venezuelan (VEEV) equine encephalitis viruses are mosquito-borne pathogens classified as potential biological warfare agents for which there are currently no approved human vaccines or therapies. We aimed to evaluate the safety, tolerability, and immunogenicity of an investigational trivalent virus-like particle (VLP) vaccine, western, eastern, and Venezuelan equine encephalitis (WEVEE) VLP, composed of WEEV, EEEV, and VEEV VLPs. Methods: The WEVEE VLP vaccine was evaluated in a phase 1, randomised, open-label, dose-escalation trial at the Hope Clinic of the Emory Vaccine Center at Emory University, Atlanta, GA, USA. Eligible participants were healthy adults aged 18–50 years with no previous vaccination history with an investigational alphavirus vaccine. Participants were assigned to a dose group of 6 μg, 30 μg, or 60 μg vaccine product and were randomly assigned (1:1) to receive the WEVEE VLP vaccine with or without aluminium hydroxide suspension (alum) adjuvant by intramuscular injection at study day 0 and at week 8. The primary outcomes were the safety and tolerability of the vaccine (assessed in all participants who received at least one administration of study product) and the secondary outcome was immune response measured as neutralising titres by plaque reduction neutralisation test (PRNT) 4 weeks after the second vaccination. This trial is registered at ClinicalTrials.gov, NCT03879603 . Findings: Between April 2, 2019, and June 13, 2019, 30 trial participants were enrolled (mean age 32 years, range 21–48; 16 [53%] female participants and 14 [47%] male participants). Six groups of five participants each received 6 μg, 30 μg, or 60 μg vaccine doses with or without adjuvant, and all 30 participants completed study follow-up. Vaccinations were safe and well tolerated. The most frequently reported symptoms were mild injection-site pain and tenderness (22 [73%] of 30) and malaise (15 [50%] of 30). Dose-dependent differences in the frequency of pain and tenderness were found between the 6 μg, 30 μg, and 60 μg groups (p=0·0217). No significant differences were observed between dosing groups for any other reactogenicity symptom. Two adverse events (mild elevated blood pressure and moderate asymptomatic neutropenia) were assessed as possibly related to the study product in one trial participant (60 μg dose with alum); both resolved without clinical sequelae. 4 weeks after second vaccine administration, neutralising antibodies were induced in all study groups with the highest response seen against all three vaccine antigens in the 30 μg plus alum group (PRNT80 geometric mean titre for EEEV 60·8, 95% CI 29·9–124·0; for VEEV 111·5, 49·8–249·8; and for WEEV 187·9, 90·0–392·2). Finally, 4 weeks after second vaccine administration, for all doses, the majority of trial participants developed an immune response to all three vaccine components (24 [83%] of 29 for EEEV; 26 [90%] of 29 for VEEV; 27 [93%] of 29 for WEEV; and 22 [76%] of 29 for EEEV, VEEV, and WEEV combined). Interpretation: The favourable safety profile and neutralising antibody responses, along with pressing public health need, support further evaluation of the WEVEE VLP vaccine in advanced-phase clinical trials. Funding: The Vaccine Research Center of the National Institute of Allergy and Infectious Diseases, National Institutes of Health funded the clinical trial. The US Department of Defense contributed funding for manufacturing of the study product.